2003
DOI: 10.1002/anie.200250181
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Piano Stools: A Molecular Recognition Motif That Enforces 1:1 Cocrystallization of Two Diastereomers in the Same Single Crystal

Abstract: Half‐sandwich complexes of the type [(Ar)MXY(NR*)] (see structure; X, Y=electronegative substituents; M=Ru, Os, Rh, Ir) tend to form inversion pairs in the solid state, which are characterized by short M⋅⋅⋅M separations and CH⋅⋅⋅X/Y hydrogen bonds between the pairs of molecules. As a consequence, two diastereomers with a given chirality in the Z substituent, usually an NR* substituent, and different metal configurations approach each other with their “racemic sides” resulting in an unusually preferred 1:1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…1 H-NOESY NMR experiments were used to determine the chirality of the metal center and cymene orientation in solution. 19 F, 1 H-HOESY NMR investigation allowed us to elucidate the interionic structure, i.e., the relative anion-cation orientations, in solution. The solid state structure of 4PF 6 was obtained through X-ray single crystal studies and compared from intramolecular and interionic points of view with that in solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H-NOESY NMR experiments were used to determine the chirality of the metal center and cymene orientation in solution. 19 F, 1 H-HOESY NMR investigation allowed us to elucidate the interionic structure, i.e., the relative anion-cation orientations, in solution. The solid state structure of 4PF 6 was obtained through X-ray single crystal studies and compared from intramolecular and interionic points of view with that in solution.…”
Section: Discussionmentioning
confidence: 99%
“…All compounds were characterized by 1 H, 13 C, 19 F, 1 H-COSY, 1 H-NOESY, 19 F, 1 H-HOESY, 1 H, 13 C-HMQC and 1 H, 13 C-HMBC NMR spectroscopies at 293 K in CD 2 Cl 2 . Numbering of atoms for 4PF 6 is shown in Chart 1.…”
Section: Intramolecular Characterization In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray crystal data for 1 (19), max. residual electron density 0.22 (-0.35) e Å -3 , hydrogen atoms calculated and refined as riding atoms, excepting the amino-group hydrogen, located from the difference Fourier map and refined isotropically.…”
Section: X-ray Structure Determinationmentioning
confidence: 99%
“…The most usual guest co-crystal components are water or other solvent molecules. The cocrystallization of stereoisomers is exhibited most often by metal complexes [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. It has been demonstrated that many of these undergo dissociation and re-coordination in solution.…”
Section: Introductionmentioning
confidence: 98%